The Impact and Importance of LLMOps for Companies Advancing Generative AI - Madhavrao, Vikhe Pramod (Journal of Global Economy, Business and Finance, 2025)
In the current landscape of artificial intelligence (AI), the emergence of large language models LLMs has catalyzed the development of generative AI applications across various industries. LLMOps, a specialized subset of MLOps (Machine Learning Operations), is gaining traction as an essential framework for managing and operationalizing LLMs at scale. This article explores the critical role of LLMOps in advancing generative AI within enterprises, addressing the complexities involved in deploying, monitoring, and maintaining these models. It further examines how LLMOps enhances collaboration between data scientists, ML engineers, and IT operations. Promoting a seamless integration of LLMs into existing enterprise infrastructures. The article also highlights the challenges and opportunities that arise with the adoption of LLMOps, offering insights into how organizations can leverage this framework to unlock the full potential of generative AI.